The burden of trauma presenting to the government referral hospital in Freetown, Sierra Leone: An observational study - Bundu, Ibrahim (Afr J Emerg Med, 2019)
INTRODUCTION: Trauma accounts for a significant proportion of the global burden of disease, with highest mortality rates seen in Africa. This epidemic is predicted to increase with urbanisation and an aim of the Sustainable Development Goals is to reduce deaths and trauma caused by road accidents. Data available on urban trauma in Sierra Leone is limited. METHODS: We conducted a retrospective observational study of trauma and injury related presentations to the emergency centre (EC) of Connaught Hospital, the principal adult tertiary referral centre in Freetown, Sierra Leone between January and March 2016. Patient demographics are described with mechanism of injury. Additional data on length of stay and surgical procedures were recorded for admissions to the trauma ward. RESULTS: During the 3-month period, a total of 340 patients with injury presented to the EC, accounting for 11.6% of total attendances and 68% of adult surgical admissions. The majority were male (66%) and mean age was 26 years (IQR 15–40). The proportion of trauma presentations were higher in the evening and at weekends and 41% of patients were triaged as emergency or very urgent cases. Road traffic accidents were the most frequent cause of injury (55%) followed by falls (17%) and assaults (14%). Burns were more common in children. Head and lower limbs were the most commonly injured body parts and a minority of patients underwent surgical procedures. Median length of stay for adult patients was 4.5 days (IQR 2–11) and 7 days (IQR 4–14) for children. DISCUSSION: Injury accounts for a high burden of disease at Connaught Hospital and consumes a significant proportion of EC and hospital resources. Efforts should be directed towards strengthening the pre-hospital and emergency trauma systems with accurate, formal data collection as well as targeting injury prevention initiatives and improving road safety to reduce morbidity and mortality.